Time-scale relationship between securitized real estate and local stock markets: Some wavelet evidence - Kim Hiang Liow; Xiaoxia Zhou; Qiang Li; Yuting Huang (Journal of Risk and Financial Management, 2019)
This study revisits the relationship between securitized real estate and local stock markets by focusing on their time-scale co-movement and contagion dynamics across five developed countries. Since securitized real estate market is an important capital component of the domestic stock market in the respective economies, it is linked to the stock market. Earlier research does not have satisfactory results, because traditional methods average different relationships over various time and frequency domains between securitized real estate and local stock markets. According to our novel wavelet analysis, the relationship between the two asset markets is time-frequency varying. The average long run real estate-stock correlation fails to outweigh the average short run correlation, indicating the real estate markets examined may have become increasingly less sensitive to the domestic stock markets in the long-run in recent years. Moreover, securitized real estate markets appear to lead stock markets in the short run, whereas stock markets tend to lead securitized real estate markets in the long run, and to a lesser degree medium-term. Finally, we find incomplete real estate and local stock market integration among the five developed economies, given only weaker long-run integration beyond crisis periods.
Keywords: 330; wavelet coherence and phase difference; rolling wavelet correlation; multiresolution analysis; contagion; securitized real estate and local stock markets